The Philosophical of the Role of the Constitutional Court Related to the Certainty of Gender Equality Rights in Indonesia - Artina, Dessy; Saragih, Geofani Milthree; Lailam, Tanto (Faculty of Law, Universitas Pattimura, 2024)
Introduction: In the agenda of the supremacy of law in Indonesia, one of the tangible manifestations carried out is the establishment of the Constitutional Court in 2003. One of the powers of the Constitutional Court is judicial review which has a major role and influence in upholding human rights. The Purposes of the Research: The purpose of this study is to analyze especially from the philosophical perspective of the role of the Constitutional Court in upholding certainty regarding gender equality in Indonesia. The main research authority is judicial review.The Methods of the Research: The research method used in this study is a normative research method with a legal and philosophical approach. The method and approach will be used in examining the role of the Constitutional Court in upholding certainty regarding gender equality in Indonesia.Results of the Research: A series of Constitutional Court decisions, including Number 22-24/PUU-VI/2008, demonstrates Indonesia's commitment to gender equality. These rulings changed election systems, ensuring equal opportunities for all candidates. The Court nullified affirmative action provisions in Law No. 10 of 2008, shifting from a 30% female representation goal. Decision Number 20/PUU-XI/2013 strengthened gender equality in politics, while Decision Number 82/PUU-XII/2014 supported women's electability in leadership roles. Decision Number 22/PUU-XV/2017 addressed gender-based discrimination in the Marriage Law. These decisions show the Constitutional Court's role in promoting gender equality, yet ongoing efforts are needed for further progress.